The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/jms.1481
|View full text |Cite
|
Sign up to set email alerts
|

Metal–ligand solution equilibria studied by electrospray ionization mass spectrometry: effect of instrumental parameters

Abstract: Electrospray ionization mass spectrometry (ESI-MS) is being increasingly employed in the study of metal-ligand equilibria in aqueous solution. In the present work, the ESI-MS spectral changes due to different settings of the following instrumental parameters are analyzed: the solution flow rate (F(S)), the nebulizer gas flow rate (F(G)), the sprayer potential (E), and the temperature of the entrance capillary (T). Twenty-eight spectra were obtained for each of six samples containing aluminum(III) and 2,3-dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
3
21
1
4
Order By: Relevance
“…Although electrospray ionization mass spectrometry (ESI‐MS) is very often employed in the study of metal/ligand equilibria in aqueous solution,1 it is well known that ESI‐MS spectra do not exactly represent the speciation picture of the solution ‘before the measurement’, due to perturbations occurring after the sample injection in the ion source and before the ion detection 1–8. In our previous work,9 these perturbations were correlated with the ESI‐MS spectral changes produced by different settings of some instrumental parameters. We concluded that these correlations allow identification of the perturbations occurring when metal‐ligand solutions are studied by ESI‐MS.…”
mentioning
confidence: 99%
“…Although electrospray ionization mass spectrometry (ESI‐MS) is very often employed in the study of metal/ligand equilibria in aqueous solution,1 it is well known that ESI‐MS spectra do not exactly represent the speciation picture of the solution ‘before the measurement’, due to perturbations occurring after the sample injection in the ion source and before the ion detection 1–8. In our previous work,9 these perturbations were correlated with the ESI‐MS spectral changes produced by different settings of some instrumental parameters. We concluded that these correlations allow identification of the perturbations occurring when metal‐ligand solutions are studied by ESI‐MS.…”
mentioning
confidence: 99%
“…Пертурбације у раствору се дешавају у капљици [12,119] у току њеног испаравања. Испаравање капљице мења концентрацију растворене врсте и сходно томе проузрокује равнотежне помераје у зависности од pH, концентрације, Т и промена јонске јачине.…”
Section: проучавање хидролизе аL(iii)-јона масеном спектрометријомunclassified
“…Међусобни однос релативне заступљености (релативни интезитет) i 763 /i 719 је сличан односу i 370 /i 326 , што указује на сличне константе комплексирања за L и L-CO 2 врсте [111,119].…”
Section: проучавање комплексирања алуминијума и флероксацина еSi мS сunclassified
See 2 more Smart Citations